A new genus and species of parasitic wasps (Hymenoptera: Diapriidae) from Hkamti mid–Cretaceous Burmese amber. (November 2020) - Jouault, Corentin; Perrichot, Vincent; Nel, André
Abstract: Protobelyta monsirei gen. et sp. nov., a new genus and species of belytine wasp (Diapriidae: Belytinae), is described from a female preserved in mid–Cretaceous Burmese (Albian–Cenomanian) amber from Hkamti. The new fossil is the first description of the family in Burmese amber and one of the oldest known Belytinae, providing evidence for the antiquity of modern diapriid lineages.